(3QSGdI aj EKHGJ GdfThIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCdJ CUdMc Gddg Cf CLYd Md eG MGWJc Hg ai BPGfg GdTchc GdeJCcOg YfOc ai JUOjb GdfThI eSCdI GdScfLjf GdeQcH ef Nd hScQ s
(3BNQgG (B:s
(3hPdc KeGfjI aEPG GLJeYJ GdKeGfjI LedI COJ Edi GdSYGOI agPG EHGfg LejY GdeSGFd Ydi GdEjLGR s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOS hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs